A sufficient and necessary condition of existence of blow-up radial solutions for a k-Hessian equation with a nonlinear operator - Xinguang Zhang; Lishan Liu; Yonghong Wu; Yujun Cui (Nonlinear Analysis, 2020)
In this paper, we establish the results of nonexistence and existence of blow-up radial solutions for a k-Hessian equation with a nonlinear operator. Under some suitable growth conditions for nonlinearity, the result of nonexistence of blow-up solutions is established, a sufficient and necessary condition on existence of blow-up solutions is given, and some further results are obtained.